S15-3: Barriers to Physical Activity Amongst Persons With Physical Disability (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The lower participation of persons with disabilities (PWD) in physical activity is not only related to health problems, but also to barriers such as the physical and social environment, personal beliefs, and motivation (Úbeda-Colomer et al., 2019). Although sports infrastructure has recently become increasingly adapted to the needs of PWD, the opportunities for PWD to participate in sports are still limited. The aim of the study was to identify and evaluate the main barriers to participation in physical activity by PWD.Methods: The study involved 54 working age (18–65 years old) persons with physical disabilities whose working capacity was not less than 25 percent. The data collection was done by using: 1) Physical Activity Scale for Individuals with Physical Disabilities (PASIPD) (Washburn et al., 2002) and 2) Barriers to Physical Activity Questionnaire for People with Mobility Impairments (BPAQ-MI) (Úbeda-Colomer et al., 2019).Results: 92.6% of the subjects had very low physical activity (PA). Women spend more time on light housework than men (U = 214.5; p = 0.009). At the interpersonal level, the inactivity of friends and family were the main barriers. Women lack support from sports centre staff ((χ² = 3) 13.671; p = 0.003) and adapted transport ((χ² = 3) 10.587; p = 0.014) more than men. There was no difference between genders in PA and the association between barriers, and an inverse correlation between PA and social connectedness was found in the total sample (p < 0.05).Conclusions: Physical activity of PWD is very low, only 7.4 percent of subjects participating in the study were physically active. The subjects pointed out these barriers to PA: fatigue, motivation, inadequate facilities, lack of sports programmes, inadequate sidewalks/streets. Analysis of the study data showed that as physical activity increases, dependence on others decreases. No significant differences in physical activity and barriers to participation in physical activity have been identified in terms of gender, except: women spend more time on light housework, women lack the help of sports centre employees, women lack accessible transportation to go to the sports centre.Keywords: Physical disability, exercise, participation